Etiology of Autism - Trajkovski, Vladimir (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2004)
Although there is good evidence that autism is a multifactorial disorder, an adequate understanding of the genetic and nongenetic causes has yet to be achieved. With empirical research findings review is made to evidence on possible causal influences. Much the strongest evidence concerns the importance of susceptibility genes, but such genes have yet to be identified. Specific somatic conditions (tuberous sclerosis and the fragile X syndrome) account for a small proportion of cases. Over recent decades there has been a major rise in the rate of diagnosed autism. The main explanation for this rise is to be found in better ascertainment and a broadening of the diagnostic concept. Progress on the elucidation of the causes of autism will be crucially dependent on the combination of epidemiology with more basic science laboratory studies.
Етиологија на аутизмот
Keywords: epidemiology, autism, genetic influences, MMR-vaccine